PENGARUH CORRUPTION DAN ECONOMIC FREEDOM TERHADAP INVESTMENT (Studi pada Negara Indonesia Tahun 2006-2016) - Arum Masyitah; Suhadak Suhadak; Ferina Nurlaily (Jurnal Administrasi Bisnis, 2018)
The purpose of this reasearch is to find out and explain the influence of corruption on investmnet, find out and expalain the influence of corruption on economic freedom, find out the economic freedom influence on investment in state of Indonesia. The type of this research is explanatory research with quantitative approach. The data used is from Corruption Eradication Commission (KPK), Heritage Foundation, Bank Indonesia, and Capital Investment Coordinating Board (BKPM) with uses time series data of corruption, economic freedom and investment Indonesia during the periods of 2006-2016 with 11 observations for sample. Data analysis technique using Partial Least Square by SmartPLS 3.2.7 application. The result of the research indicate : insignificant influence of corruption towards investment, significant influence of corruption to economic freedom, significant between economic freedom towards investment. Keyword : Corruption, Economic Freedom, Foreign Direct Investment, Domestic Direct Investment ABSTRAK Tujuan penelitian ini adalah untuk mengetahui dan menjelaskan pengaruh Corruption terhadap Investment, Corruption terhadap Economic Freedom, pengaruh Economic Freedom terhadap Investment pada Negara Indonesia. Jenis penelitian ini adalah explanatory research dengan pendekatan kuantitatif. Sumber data berasal dari Komisi Pemberantasan Korupsi (KPK), Heritage Foundation, Bank Indonesia, dan BKPM dengan menggunakan data time series dari Corruption, Economic Freedom dan Investment Negara Indonesia periode tahun 2006-2016 dengan jumlah sampel sebanyak 11 pengamatan. Teknik analisis data menggunakan Partial Least Square (PLS) dengan menggunakan aplikasi SmartPLS 3.2.7. Hasilnya menujukkan bahwa tidak terdapat pengaruh signifikan antara Corruption terhadap Investment, terdapat pengaruh signifikan antara Corruption terhadap Economic Freedom, terdapat pengaruh signifikan antara Economic Freedom terhadap Investment. Kata Kunci : Korupsi, Kebebasan Ekonomi, Investasi Asing Langsung, Investasi Domestik Langsung